‘Modest’ and ‘Faithful’: Centering Pseudonyms in Fiction in Early Twentieth Century Chinese Periodicals - Zhenkai Tong (Janeway JS, 2021)
In this article, I attempt to show that literary works produced by authors who have their identities hidden behind pseudonyms may further current understandings of the May Fourth and New Culture literary canon. I examine two fictional short stories, written by Xuxin (‘Modest’) and Zhongyan (‘Faithful’), and explore how these short stories reinforce or nuance established understandings of the May Fourth and New Culture canon. I examine their works within the context of the May Fourth and New Culture movements and attempt to offer a comparative analysis of these two short stories, while suggesting that more attention should be given to authors whose identities were hidden.